Menuju Fakultas Syariah yang Unggul, Mandiri dan Trendi Dipersaingan Global - Kamaruddin Kamaruddin (Institut Agama Islam Negeri (IAIN) Kendari, 2009)
Syari’ah faculty is the including eldest faculty of PTAIN in Indonesia proving a efficacy of him. Because have tested by varying the collegiate of have spread over occupy an important position at the same time give a medial benefit of society. More than anything else enter century which to 21, the tendency of society progressively give chapter and verse, for example, terms appearance of syari’ah which not only Moslem interest to wear that name, but outside just Islam also isn’t it the term namely, the economics of syari’ah, and so on. However, all that, have to be strengthened by a peripheral supporting him, for example strengthening the science (statistic, accountancy of syari’ah and his him), so that does not simply name without giving meaning. He/She can exceed in emulation, and can self-supporting and also can trend in the middle of society if can take care of and prove principles which implied in Moslem law values. So that reinforcement of science become is obliged to ain continue to be corrected.